FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENYULUH PERTANIAN DI KABUPATEN KONAWE (FACTORS AFFECTING PERFORMANCE OF AGRICULTURAL EXTENSION WORKERS IN KONAWE DISTRICT) - Syafruddin, Syafruddin; Hariadi, Sunarru Samsi; Wastutiningsih, Sri Peni (Jurnal Ilmu-Ilmu Pertanian, 2013)
This study aimed to know how much the given influences of the factors of job motivation, ability, level of education, years of service, promotion, training frequencies, and support of the infrastructures to the performance of agriculture extension workers in the district of Konawe. The used analyzing unit in this study was agriculture extension workers, sample was analyzed and processed as the respondents by conducting census that were all of existing officers of agriculture extension workers (130 officers), whereas sample of farmers was determined purposively of 2 farmers who lived in the developping area of agriculture extension workers and they were respondents, thus total of them were 260 farmer. Then, the data was analyzed using statistic test of path analysis from Amos 16.0. Based on the study results, it showed that (1) factor of job motivation and level of education of the extensioner influenced significantly to the performance of the agriculture extensioner workers, (2) factor that explained in sufficiently high the level of performance of the agriculture extension workers was job motivation, (3) factor of level of education of the extensioner was the starting point of the role of promotion, training frequencies, ability, and job motivation of the agriculture extensioner workers.